Determination of Triamcinolone Acetonide Steroid on Glassy Carbon Electrode by Stripping Voltammetric Methods - C. Vedhi, R. Eswar, H. Gurumallesh Prabu and P. Manisankar (International Journal of Electrochemical Science, 2008)
A corticosteroid, triamcinolone acetonide was determined by stripping voltammetric procedure using glassy carbon electrode. Cyclic voltammetric behaviour of steroid was studied in 50% aqueous methanol at acid, neutral and alkaline pH conditions. Influence of pH, sweep rate and steroid concentration were studied. An irreversible and adsorption-controlled well-defined reduction peak was observed in all pH conditions. The reduction peak potential shifted cathodically with change in pH. Controlled potential coulometry revealed two-electron reduction of the a,b-unsaturated carbonyl function present in the steroid. A systematic study of the experimental parameters that affect the differential pulse / square wave stripping voltammetric response was carried out and optimized conditions were arrived at. Under optimum conditions, differential pulse and square wave adsorptive stripping voltammetric procedures were developed for the determination of triamcinolone acetonide steroid at pH 13.0. A calibration plots was derived and the lower limit of determination observed are 0.1 mg/mL from DPSV and 0.01 mg/mL from SWSV.